2021
DOI: 10.1088/1755-1315/685/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Campus Operational Carbon Assessment Based on Low Carbon City Framework (LCCF)

Abstract: Universiti Teknologi MARA (UiTM) is Malaysia’s largest institution of higher learning (IHE). The university is based on 13 state campuses and 21 satellite campuses. The state of Selangor has the largest number of UiTM campuses, and the main anchor campus is located in the state capital, Shah Alam. As for UiTM which is committed to implement the low carbon cities framework program focusing on five GHG reduction elements through energy, mobility, waste, water; and greenery and water bodies. This study reveals th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The university has 13 state campuses and 21 satellite campuses. The efforts focused on five greenhouse gas (GHG) reduction elements, namely energy, mobility, waste, greenery, and water bodies, using a city-based approach within the Low Carbon City Framework (LCCF), including the urban environment, urban infrastructure, and building criteria [50].…”
Section: Discussionmentioning
confidence: 99%
“…The university has 13 state campuses and 21 satellite campuses. The efforts focused on five greenhouse gas (GHG) reduction elements, namely energy, mobility, waste, greenery, and water bodies, using a city-based approach within the Low Carbon City Framework (LCCF), including the urban environment, urban infrastructure, and building criteria [50].…”
Section: Discussionmentioning
confidence: 99%
“…In achieving sustainability and carbon neutrality in higher education institutions study conducted by Sen et al [11], it is found that the amount of carbon emissions (MtCO2) released on campus is about 11,658 MtCO2 and the energy sources contributing to carbon emissions on campus are fossil fuels and electricity [12].…”
Section: Overview Of Carbon Emission By Energy Usagementioning
confidence: 99%